Features of law enforcement practice in the collection and evaluation of evidence to protect the social rights of police officers - M. A. Sambor (Law and Safety)
The law enforcement practice of judicial bodies, namely administrative courts of different instances, regardless of their territoriality, in resolving administrative disputes concerning the protection of social rights of police officers to receive additional surcharges during quarantine is analyzed. The starting point is the understanding of the content and importance of social protection for the use of social rights of police officers. The importance of the state to create positive guarantees of social protection for the use of social rights by the police is analyzed. Particular attention is paid to the formation of a system of state guarantees for the protection and safeguarding of social rights of police officers, due to the performance of the latter functions of the state in accordance with the tasks facing this state executive body both in daily activities and during quarantine which poses additional threats to the life and health of a police officer. The peculiarities of proving and gathering evidence on establishing legal facts related to the exercise of police powers to ensure life in quarantine and the presence of direct contact of the police officer with the public as a result of their exercise of power. Attention is paid to taking into account during the drafting of court decisions the peculiarities of the use of law to formulate judicial positions to substantiate or refute the legal positions of the parties to the administrative case. The peculiarities of the sources of evidence in the construction of the legal position of protection of social rights of police officers, including the receipt of additional surcharges to the financial security during quarantine, are formulated. Proposals on the use of documents, as well as high-quality motivation of the actual circumstances of the performance of police duties in quarantine, related to the livelihood of the population, the provision of services and law enforcement are analyzed and provided. The disregard in legal positions, and, consequently, when motivating court decisions, the provisions of the Constitution of Ukraine and the Law of Ukraine "On the National Police" is justified.